PANDANGAN KAUM SALAFI RAUDLATUL AMIN DESA KETAPANG DAYA TERHADAP PEMILIHAN UMUM DI KABUPATEN SAMPANG - Hakim, Arief Rahmanul (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This articlehas been written based on the research about political attitudes of the salafi members of majelis taklim Raudlatul Amin in Ketapang Daya, Sampang on democracy and elections in Indonesia. Using qualitative approach the study aims to answer two main questions, are; first, how are the perceptions of the Salafi group about elections in Indonesia? Second, how do the salafi members perceive the mechanism of electing the leaders? The study has resulted in two main conclusions are: first, to the salafi members of majelis taklim Raudlatul Amin Ketapang, democratic system,in which leaders are elected through elections wherethe winner is decided based on the majority vote, is incompatiblewith the Islamis teachings. Second, this group argues that the mechanism of electing leaders should conform with that of mechanism exemplified by Salaf as-Salih, namely the models of nomination or hereditary.